Comparisons of Clinical Features in Japanese Patients with Behçet's Uveitis Treated in the 1990s and the 2000s. (17th February 2020) - Nakahara, Hisae; Kaburaki, Toshikatsu; Tanaka, Rie; Yoshida, Atsushi; Takamoto, Mitsuko; Kawata, Mikiko; Fujino, Yujiro; Kawashima, Hidetoshi; Aihara, Makoto
ABSTRACT: Purpose : We investigated clinical characteristics of ocular Behçet's disease (BD) patients treated in the 1990s and the 2000s. Methods : We retrospectively examined records of 68 newly arrived patients with ocular BD followed for more than 4 months during the 2000s and compared to those of 107 patients during the 1990s. Patient profiles, ocular and systemic symptoms, frequency of ocular attacks, BD ocular attack score 24–6 months (BOS24-6M), best-corrected visual acuity (BCVA), and immunomodulatory treatment were noted. Results : Clinical characteristics in the 2000s showed increases in iridocyclitis type, intestinal-, vasculo-, and neuro-BD cases, oral corticosteroid, methotrexate, and infliximab therapy usage, cataract and glaucoma surgery, and pseudophakia, and decreases in BOS24-6M and cyclophosphamide usage. BCVA of 20/30 or better at the final visit was slightly increased in the 2000s. Conclusions : Milder ocular BD tendency was seen in cases in the 2000s, whereas the incidence of special type of BD might be increasing.